Decoherence and Disorder in Quantum Walks: From Ballistic Spread to Localization - Schreiber, A.; Cassemiro, K. N.; Potoček, V.; Gábris, A.; Jex, I.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Highly Efficient Single-Pass Source of Pulsed Single-Mode Twin Beams of Light - Eckstein, Andreas; Christ, Andreas; Mosley, Peter J.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Experimental Observation of Quantum Talbot Effects - Song, Xin-Bing; Wang, Hai-Bo; Xiong, Jun; Wang, Kaige; Zhang, Xiangdong; Luo, Kai Hong; Wu, Ling-An (Physical Review Letters)

All Nonclassical Correlations Can Be Activated into Distillable Entanglement - Piani, Marco; Gharibian, Sevag; Adesso, Gerardo; Calsamiglia, John; Horodecki, Paweł; Winter, Andreas (Physical Review Letters)
We devise a protocol in which general nonclassical multipartite correlations produce a physically relevant effect, leading to the creation of bipartite entanglement. In particular, we show that the relative entropy of quantumness, which measures all nonclassical correlations among subsystems of a quantum system, is equivalent to and can be operationally interpreted as the minimum distillable entanglement generated between the system and local ancillae in our protocol. We emphasize the key role of state mixedness in maximizing nonclassicality: Mixed entangled states can be arbitrarily more nonclassical than separable and pure entangled states.

Quantized Magnetic Confinement in Quantum Wires - Tarasov, A.; Hugger, S.; Xu, Hengyi; Cerchez, M.; Heinzel, T.; Zozoulenko, I. V.; Gasser-Szerer, U.; Reuter, Dirk; Wieck, A. D. (Physical Review Letters)

Spin Noise of Electrons and Holes in Self-Assembled Quantum Dots - Crooker, S. A.; Brandt, J.; Sandfort, C.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review Letters)

“Artificial Atoms” in Magnetic Fields: Wave-Function Shaping and Phase-Sensitive Tunneling - Lei, Wen; Notthoff, Christian; Peng, Jie; Reuter, Dirk; Wieck, Andreas; Bester, Gabriel; Lorke, Axel (Physical Review Letters)

Entropy Explains Metal-Insulator Transition of the Si(111)-In Nanowire Array - Wippermann, S.; Schmidt, Wolf Gero (Physical Review Letters)

Probing the Negative Wigner Function of a Pulsed Single Photon Point by Point - Laiho, Kaisa; Cassemiro, Katiúscia N.; Gross, David; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Photons Walking the Line: A Quantum Walk with Adjustable Coin Operations - Schreiber, A.; Cassemiro, K. N.; Potoček, V.; Gábris, A.; Mosley, P. J.; Andersson, E.; Jex, I.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy